Quality Control in Various Sectors: A Systematic Review of Organizational Strategy, Implementation, and Performance Evaluation - Riyantama Ibnu Agil; Bima Andriano Lanove; Gresela Natasya Aulia El Mufidah; Mua’limin (Penerbit Hellow Pustaka, 2025)
Quality control is a crucial issue in efforts to improve organizational effectiveness and efficiency, across the industrial, educational, and public management sectors. The challenges of globalization and the demands of increasingly high quality standards require every institution to implement a measurable and sustainable control system. This study aims to systematically review various studies related to the implementation of quality control and answer the question: how are quality control strategies implemented and adapted in various institutional contexts? The method used is a literature review with a qualitative approach. Data were obtained from the Google Scholar and Publish or Perish (PoP) databases using the keyword quality control, with a publication period of 2020–2025. Of the 20 articles found, 7 were selected for in-depth analysis after undergoing a screening and validation process. The results of the study reveal three main themes: (1) industrial quality control based on Statistical Quality Control for production efficiency, (2) educational quality control as an instrument for improving learning quality, and (3) organizational quality control as a mechanism for accountability and strategic evaluation. This synthesis emphasizes the importance of an integrative approach between evaluation, innovation, and continuous improvement. Future research should focus on developing a cross-sectoral adaptive quality control model.